2002
DOI: 10.1023/a:1013962328048
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Oligomerization of amino acids proceeded on or inside lipid vesicles as a model of prebiotic cells in a simulated hydrothermal environment. When the suspension of lipid vesicles taking up monomeric glycine underwent a sudden temperature drop by traversing from a hot (180 degrees C) to a cold (0 degree C) region repeatedly while circulating through a closed reaction circuit, oligopeptides up to heptaglycine were formed even in the absence of condensing agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 14 publications
2
34
0
2
Order By: Relevance
“…Tsukahara et al 2002) Impact-induced hydrothermal systems may have been the only means to have generated sustained hydrothermal systems for prebiotic reactions. A schematic of the processes occurring in a crater is shown in figure 1.…”
Section: A Scheme For the Origin Of Life Within Impact Cratersmentioning
confidence: 99%
“…Tsukahara et al 2002) Impact-induced hydrothermal systems may have been the only means to have generated sustained hydrothermal systems for prebiotic reactions. A schematic of the processes occurring in a crater is shown in figure 1.…”
Section: A Scheme For the Origin Of Life Within Impact Cratersmentioning
confidence: 99%
“…Several advantages can be cited to use simulated submarine hydrothermal vent conditions as prebiotic environment: the biomolecules and biopolymers were protected from UV rays of the sun, the gradient of temperature provides energy and different sites for different reactions, at high temperature and high pressure the water behavior like an organic solvent and salts of seawater, transition metals and clays of hydrothermal vents catalyze the syntheses of biomolecules and biopolymers. 14,15 Under hydrothermal conditions, the syntheses of biomolecules, [15][16][17] biopolymers 15,[18][19][20][21][22] and microspheres, 15,22 was obtained. The prebiotic environments that could be corresponding of laboratory experiments of reaction of substances in solid state are: cooling lava from volcanoes on the ground and impact of bolides (meteor, comet) on the earth.…”
Section: Introductionmentioning
confidence: 99%
“…When 100 mM glycine was included, glycine dimers and trimers were detected, suggesting that peptide bonds were thermodynamically favored at high temperature, then preserved by quenching. Significantly, it was observed that including oleic acid, a self-assembling amphiphile, markedly enhanced the yield by 15-fold [12].…”
Section: Interactions With Amino Acidsmentioning
confidence: 99%